Thermo-mechanical characterization of passive stress sensors in Si interposer. Issue 5 (April 2015) - Vianne, Benjamin; Bar, Pierre; Fiori, Vincent; Gallois-Garreignot, Sébastien; Ewuame, Komi Atchou; Chausse, Pascal; Escoubas, Stéphanie; Hotellier, Nicolas; Thomas, Olivier
Highlights: Passive stress sensors are embedded in an interconnect level of a silicon interposer. Their innovative design is based on a rosette-shape of eight copper serpentines. Impact of elaboration processes on sensors is characterized. A methodology was built up to numerically extract gauge factors of serpentines. Sensors sensitivity is assessed using four-point bending and electrical measurement. Abstract: Thermo-mechanical stress is a major concern in the frame of 2.5D integration. Passive stress sensors were integrated in a silicon interposer test vehicle to quantify stress at critical locations. The sensors were integrated in a rosette-shape consisting of eight oriented copper serpentines acting like strain gauges. This innovative design allows the calculation of a partial stress tensor, including three planar and one out-of-plane components. Electrical measurements at wafer level, combined with FIB/SEM cross-sections, revealed a strong impact of elaboration processes on the structures electrical characteristics. Numerical simulations using finite element analysis were built to evaluate the sensitivity of copper serpentines to mechanical stress. Finally a dedicated four-point bending tool coupled with a four-terminal resistance measurement setup was fabricated to experimentally extract the values of sensors sensitivity factors. Preliminary results depicted in this paper highlight a sensitivity to stress of distinctly oriented resistors. Several identified sources of data dispersion are inherent to the present measurement configuration. Added-value and limitations of such sensors were underlined, and recommendations regarding the testing strategy were drawn to allow a reliable estimation of the stress fields.